Enhancing interprofessional ward rounds by identifying factors associated with low satisfaction and efficiency: a quantitative and qualitative national survey of Swiss healthcare professionals - Armon Arpagaus; Aron Strub; Rahel Kuster; Christoph Becker; Sebastian Gross; Flavio Gössi; Eliska Potlukova; Stefano Bassetti; Drahomir Aujesky; Philipp Schuetz; Sabina Hunziker (Swiss Medical Weekly)
AIMS OF THE STUDY: Interprofessional ward rounds are a cornerstone of patient-centred care for medical inpatients and offer opportunities to discuss and coordinate patient treatment and further management. We aimed to identify factors associated with lower satisfaction and efficiency of interprofessional ward rounds, as reported by physicians and nurses.